Cultural digitalization and global health crisis - Parera, Cecilia (Universidad Nacional del Litoral, 2020)
The article analyzes the transformations that the architect´s role has verified in recent decades within the framework of the cultural digitization process, in general, and the incorporation of technological innovations in their professional practice, in particular, understanding that a large part of the conceptual references over which the discipline has been built have lost their validity. In turn, it investigates how the measures taken by most States in the face of the recent Covid 19 pandemic have forced changes in the tasks carried out by professionals, urgently promoting new forms of work and communication. The objectives are approached from an epistemological position that avoids deterministic, cumulative and linear readings about science and technology, preferring an integrative and strategic perspective. Based on the analysis of the described phenomena, and taking as an interpretive reference both research work and the opinion of numerous stakeholders, the article identifies an unprecedented context, with new possibilities towards more dynamic practices in their structure, competitive in their costs, digitally trained and predisposed to collaborative and interdisciplinary work.